A Study On Structural Stability Of Bismuth Titanate With Lanthanum Doping For Improved Ferroelectric Properties - Haji Azlan, Umar Al-Amani; Mohd Noor, Ahmad Fauzi (Indian Academy Of Sciences, 2017)
Bismuth titanate (Bi4Ti3O12) with different lanthanum (La) concentrations (0.25, 0.50, 0.75 and 1.0 mol%) was successfully prepared via soft combustion route. It was found that the change of diffraction peaks shown by X-ray diffraction is attributed to the doping effect in Bi4Ti3O12. This was also supported by the presence of additional peak that corresponds to La in the range of 800–860 eV, proved by X-ray photoelectron spectroscopy. In addition, the enlarged region of Bi 4f, Bi 4d, Ti 2p, La 3d and O 1s of doping sample was clearly seen after deconvolution. Based on binding energy position, it can be unambiguously stated that the Ti ions in the tetravalent state are surrounded by the perovskite layer of Bi4Ti3O12, which may also imply the formation of oxygen vacancies in the vicinity of the Bi2O2 layer. In comparison with Bi4Ti3O12, the green emission intensity was abruptly decreased with La doping. This indicates that La doping suppresses the formation of oxygen vacancies by stabilizing the adjacent oxide ions. Thus, the improved polarization shown by ferroelectric hysteresis loop is associated with the reduction in oxygen and bismuth vacancies due to La doping.